Educating Islamic Financial Literacy Through Enhancing Understanding Of Tabarru' Funds In Islamic Insurance - Harahap, Nurhayati; Dharmawan, Annisa Zahrina; Harahap, Salwa Hayati; Sagala, Putri Wulandini (Jurnal Abdi Mas Adzkia, 2024)
This community service program addresses the lack of public understanding regarding the management of tabarru' funds in Islamic insurance and their significance within the framework of Sharia principles. Tabarru' funds, characterized by mutual cooperation and solidarity, are pivotal to Islamic insurance and differentiate it from conventional systems. However, limited public awareness has hindered the optimal use and adoption of these products.Through structured activities such as workshops, interactive discussions, and case study analyses, this program aimed to enhance participants' understanding of tabarru' funds and their role in fostering economic resilience. Conducted in collaboration with Islamic insurance practitioners and community leaders in Medan, the program emphasized the practical benefits of tabarru' funds and their alignment with the Fatwa of the National Sharia Council-Majelis Ulama Indonesia (DSN-MUI) No. 53/DSN-MUI/III/2006. The program resulted in a notable improvement in participants' literacy regarding tabarru' funds, as evidenced by a 45% increase in understanding through pre-test and post-test assessments. Participants expressed enhanced confidence in utilizing Islamic insurance products and a deeper appreciation for the principles of mutual aid and financial solidarity. Beyond individual learning outcomes, the program strengthened community engagement with Islamic financial principles, contributing to inclusive and sustainable economic practices. This initiative highlights the importance of educational efforts in bridging the gap between theoretical knowledge and practical applications of Islamic finance. By addressing specific challenges in tabarru' fund literacy, it lays the foundation for a more informed and financially resilient society